Estimated differences in economic and environmental performance of forage-based dairy herds across the UK - Bell, Matthew J.; Wilson, Paul (Wiley Open Access, 2018)
Differences in performance among the areas of England, Scotland, Wales and Northern Ireland can provide some insight into the resilience of UK milk supplies from forage-based dairy herds. This study used a Markov Chain approach to model the average herd in each region between the years 2010 to 2015. The effect of a single unit change in milk production (milk volume, fat yield and protein yield), fitness (survival, somatic cell count, mastitis and calving interval) and efficiency (methane) traits on the economic value and GHG emissions intensity (expressed as carbon dioxide equivalents per cow and per kg milk solids) were assessed. Production data were obtained from a total of about half a million milk recorded dairy cows in the UK and the Farm Business Surveys for each region. Across the UK improving the health (SCC and mastitis), fertility (calving intervals) and survival of cows will increase profitability and reduce emissions intensity of milk production. In Scotland, herds had higher milk yields but poorer survival, which potentially could be due to poor fertility indicated by a longer calving interval compared to other regions. Herds in Northern Ireland had the shortest average calving interval but the highest somatic cell counts (SCC), and thus greater estimated mastitis incidence and wasted milk. Notably, England had considerably higher economic values (between 10 and 30%) and emission intensity values (between 11 and 37%) for SCC and mastitis incidence than other regions, due to lost milk production and the higher gross margin. This study provides a framework that can be customised for individual herds to allow assessment of resilience and resource efficiency of milk production not only in the UK but for comparison with international dairy systems.